Comparative Study: Yoga and Pregnancy Exercise on First Stage Pain and Length of Labor in Tapanuli Regency - Ganda Agustina Hartati Simbolon; Ns. Tiur Romatua Sitohang; Elny Lorensi Silalahi (Postgraduate, University of Mataram, 2023)
Labor pain is pain that comes from uterine contractions trying to expel the baby. The mother's perception of pain during labor can influence the length of the labor process. Pregnant women should be supported to carry out physical exercise to obtain benefits during pregnancy and childbirth. There are several physical exercises during pregnancy, which pregnant women often participate in, such as pregnancy exercises and pregnancy yoga. The aim of this research is to develop yoga exercises and pregnancy exercises to overcome pain in the first stage and duration of labor, as well as to conduct a trial of a combination of yoga exercises and pregnancy exercises which can be developed to reduce pain in the first stage and duration of labour. This study used a prospective cohort design with consecutive sampling technique. The research subjects were pregnant women in the third trimester who were in the working area of North Tapanuli and Central Tapanuli Regencies. The research sample consisted of 50 people taking part in pregnancy exercise and 50 people taking part in pregnancy yoga during April - June 2023. Data analysis used the Mann Withney test. The Mean Rank value for duration of labor for respondents who did yoga exercise was 44.70 and for respondents who did pregnancy exercise was 56.30. Based on the results of statistical tests, a p value of 0.044 was obtained. The Mean Rank value of labor pain for respondents who did yoga exercise was 32.80 and for respondents who did pregnancy exercise was 68.20. Based on the results of statistical tests, a p value of 0.000 was obtained. so it can be concluded that there is a difference in the length of labor and labor pain between pregnant women who were given yoga training and pregnant women who were given pregnancy exercise training.